Goodnight, my love! = [book with audioplayer] Chalcha, nae sarang! - Admont, Shelley ([Library Ideas, LLC], 2021)
English Korean Bilingual children's book. Perfect for kids studying English or Korean as their second language. "Goodnight, My Love!" by Shelley Admont won the Gold Medal in 2019 Readers' Favorite annual international book award in the Children - General category Alex finds it hard to go to sleep, so he starts making up excuses. After reading a bedtime story, his father suggests planning a dream that he would like to see when he falls asleep. Find out where their imagination takes them as they plan his dream together. This bedtime story will help kids feel loved and relaxed, preparing them for a peaceful, sleep-filled night.